Functional xylem anatomy of aspen exhibits greater change due to insect defoliation than to drought. (3rd July 2018) - Hillabrand, R M; Lieffers, V J; Hogg, E H; Martínez-Sancho, E; Menzel, A; Hacke, U G
Abstract: The study of tree rings can reveal long-term records of a tree's response to the environment. This dendroecological approach, when supplemented with finer-scale observations of the xylem anatomy, can provide novel information about a tree's year-to-year anatomical and hydraulic adjustments. Here we use this method in aspen ( Populus tremuloides Michx.) to identify xylem response to drought and insect defoliation. Surprisingly, we found that precipitation influenced vessel diameter mostly in the trees' youth, while this correlation was less pronounced at maturity. This is likely due to a reduction in stress the stand experiences as it ages, and reflects an ability to mediate drought stress as trees mature. Defoliation events caused consistent and profound changes in fiber anatomy likely leading to reduced structural support to vessels. We therefore expect that in years of defoliation trees may be vulnerable to drought-induced cavitation when leaf area recovers. This study highlights how the inclusion of cellular level measurements in tree ring studies provides additional information on how stress events may alter tree functioning through alterations in structure.